2018
DOI: 10.1042/bsr20171731
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal hypothyroidism during pregnancy on insulin resistance, lipid accumulation, and mitochondrial dysfunction in skeletal muscle of fetal rats

Abstract: The present study aimed to investigate the effect of maternal hypothyroidism during pregnancy on thyroid function of the fetal rat. Female Sprague–Dawley rats were randomized into two groups. Propylthiouracil (PTU) group received PTU in drinking water for 6 weeks (n=90), normal group received normal drinking water (n=50). The pregnant rats were obtained and had a cesarean-section to get at gestational ages of 8.5, 13, and 21 days, following blood samples and skeletal muscle were obtained from fetal rats. Level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(28 reference statements)
1
5
2
Order By: Relevance
“…While THs are known to affect mitochondrial biogenesis and function postnatally 26 , 27 , only one previous study to our knowledge has investigated the effects of prenatal THs on mitochondrial parameters in a hypothyroid rat model. This study found no clear effects of prenatal THs on mitochondrial traits 29 . Furthermore, mitochondria are generally responsive to varying (both high and low) ambient temperature (reviewed in 28 ).…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…While THs are known to affect mitochondrial biogenesis and function postnatally 26 , 27 , only one previous study to our knowledge has investigated the effects of prenatal THs on mitochondrial parameters in a hypothyroid rat model. This study found no clear effects of prenatal THs on mitochondrial traits 29 . Furthermore, mitochondria are generally responsive to varying (both high and low) ambient temperature (reviewed in 28 ).…”
Section: Resultscontrasting
confidence: 82%
“…Mitochondrial density and bioenergetics are likely to be influenced by THs across taxa ( 25 , 26 , reviewed in 27 ) and by ambient temperature 28 . However, to our knowledge, the effects of prenatal THs on mitochondria have not been characterized beyond mammalian models 29 . (3) Finally, we measured biomarkers of oxidative stress, the imbalance between oxidizing molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While THs are known to affect mitochondrial biogenesis and function postnatally (25,26), only one previous study to our knowledge has investigated the effects of prenatal THs on mitochondrial parameters in a hypothyroid rat model. This study found no clear effects of prenatal THs on mitochondrial traits (28).…”
Section: Resultscontrasting
confidence: 82%
“…Mitochondrial density and bioenergetics are likely to be influenced by THs across taxa (24, 25, reviewed in 26) and by ambient temperature (27). However, to our knowledge, the effects of prenatal THs on mitochondria have not been characterized beyond mammalian models (28).…”
Section: Introductionmentioning
confidence: 99%
“…Further related animal experiments suggested that not only fetal/neonatal hyperinsulinemia but also fetal/neonatal insulin resistance can be induced by various maternal gestational interventions. It was reported that insulin resistance in offspring can be induced by gestational interventions such as high-fat diets (4648), high-fructose diets (49), malnutrition or nutrition deficiency (50, 51), chronic intermittent hypoxia exposure (52, 53), abnormal levels of hormones (5456), chemical or drug induction (5759), and diabetic induction by genetic or non-genetic factors (60). Besides diabetes models, offspring hyperinsulinemia exists without maternal hyperglycemia in some other rodent animal experiments above (61, 62).…”
Section: Fetal Metabolic Programmingmentioning
confidence: 99%